Ordinal to Cardinal positional transformation of need hierarchy - Chakraborty, Soma; Konwar, Juthika; Pandit, Abhijit (The journal of contemporary issues in business and government, 2021)
The drive to get an action accomplished is motivation. The combination of needs, drives and outcomes gets the action to move and this consolidated action is called motivation. Motivation helps judge the attractiveness of a stimulus. The knowledge of the determinants of motivation is very important for the study of motivation. The study of motivation reaches its proper significance when the works of Abraham Maslow is studied. The theory of needs answers variety of questions when motivation is to be studied. The significance of need accomplishment according to the hierarchy ladder of need as propounded by Maslow when studied in connection with consumer’s want for buying a house under the parameters of ordinal scale, receives a new paradigm when converted to the cardinal scale. The present research paper studies the consumer motivation factors according to the categories of consumers based on demography and converts the data from ordinal form to cardinal form. The conversion of data type helps the understanding and study of the data better. Where constituents of the respondent type unwrap the need hierarchy and carry the study of motivation to an elevated level.